Agreement between clinical and histopathologic diagnoses and completeness of oral biopsy forms - Mendez, M.; Haas, A. N.; Rados, P. V.; Sant'ana, M. Filho; Carrard, V. C. (Braz Oral Res, 2016)
The present study aimed to assess the rate of agreement between clinical and histopathological diagnoses and to report the frequency of completed forms for specimens that were subjected to histopathological examination and retrospectively examined. Data from 8,168 specimens submitted to histopathological examination were retrieved from the records. A total of 5,368 cases were included. Agreement was defined based on the definition of lesion nature according to its diagnostic category. Sensitivity, specificity, and positive and negative predictive values were calculated for each diagnostic category. The highest rate of agreement was observed for periapical lesions (92.6%), followed by potentially malignant disorders (90.1%) and non-neoplastic proliferative disorders (89.3%). Low rates of histopathological confirmation of the clinical impression were observed for mesenchymal tumors (25.0%) and cysts (44.2%). Sensitivity values were > 0.70 for all lesions, except for cysts (0.51). Specificity was relatively high, ranging from 0.97 to 1.00. The frequency of incomplete biopsy forms ranged from 16.8% (malignant tumors of oral mucosal epithelium) to 51.0% (nonspecific inflammatory reaction). The most frequently completed biopsy forms corresponded to epithelial malignant tumors (83.2%) and glandular inflammation (72.3%). In conclusion, there was an acceptable level of agreement. The low level of completeness of biopsy forms indicates little awareness about the relevance of gathering detailed information during clinical examination.
Mendez, MarinaHaas, Alex NogueiraRados, Pantelis VarvakiSant'ana, Manoel FilhoCarrard, Vinicius CoelhoengBrazilBraz Oral Res. 2016 Aug 22;30(1):e94. doi: 10.1590/1807-3107BOR-2016.vol30.0094.
Keywords: Biopsy/methods; Diagnostic Errors; Female; Humans; Male; Mouth Diseases/*pathology; Mouth Mucosa/pathology; Mouth/*pathology; Reference Values; Retrospective Studies; Sensitivity and Specificity